Simulated clinical scenario of basic life support for adults in a hospital context: an integrative review - Camila Gomes Carvalho; Cláudio César Guimarães Martins; Iorana Candido da Silva; Renata Marinho Fernandes; Juliane Rangel Dantas; Ana Railka Oliveira-Kumakura; Ana Luisa Brandão de Carvalho Lira (Rev Rene)
Objective: to identify the content and materials necessary to compose a simulated clinical scenario of basic life support for adults in a hospital context. Methods: integrative review, carried out in five databases: MEDLINE, Web of Science, SCOPUS, LILACS, and CINAHL, with no specific time frame or language, using the descriptors "Simulation Training" e "Cardiopulmonary Resuscitation". Results: the 15 articles selected were published in English, from 2015 to 2023. The content found included: chest compression depth, chest compression rate, chest indentation, chest compression fraction, hand positioning, and teamwork. The materials needed included: training manikins/simulators, stepladders, and timekeeping devices. Conclusion: the essential elements needed to create basic life support scenarios are divided into content and materials. Supplies, parameters for cardiac arrest, organization, and team coordination stood out. Contribution to practice: our findings may help build simulated scenarios related to basic life support, for the permanent education of health care teams and to train new professionals.